2017
DOI: 10.1061/(asce)he.1943-5584.0001534
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Four Extensive Green Roof Design Variables on Stormwater Hydrology

Abstract: This study assesses the relative influence of four independent variables on green roof hydrological performance under rainstorm conditions. Twenty-four extensive green roofs representing all combinations of the following four design factors were used: native meadow species versus Sedum; mineral-based versus biologically derived planting medium; 10-cm versus 15-cm depth; and irrigation provided daily, sensor controlled, or not at all. From events covering the period May-October in 2013 and 2014, mean values wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Modeling approaches have advanced in number and sophistication since 2007, when Elliot and Trowsdale [26] reported that only one model (e.g., Water Balance Model) could be used to model green roof hydrology explicitly. Recent modeling efforts represent green roof storm water attenuation using runoff coefficients or curve numbers [27][28][29][30] and use more elaborate physically-based models such as HYDRUS-1D (Prague, Czech Republic) [31][32][33] to represent saturated and unsaturated flow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling approaches have advanced in number and sophistication since 2007, when Elliot and Trowsdale [26] reported that only one model (e.g., Water Balance Model) could be used to model green roof hydrology explicitly. Recent modeling efforts represent green roof storm water attenuation using runoff coefficients or curve numbers [27][28][29][30] and use more elaborate physically-based models such as HYDRUS-1D (Prague, Czech Republic) [31][32][33] to represent saturated and unsaturated flow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Green roofs help reduce peak storm flows and volumes discharged to storm and combined sewer systems (Nawaz et al, 2015). On an annual basis, extensive green roofs can capture, store, and evapotranspire 40 to 70% of the total precipitation (Fassman‐Beck et al, 2016; Hill et al, 2017). Extensive green roofs comprise a layer of lightweight, typically soilless, planting medium, to a maximum depth of 15 cm, that is used to support the growth of plants (Czemiel Berndtsson, 2010).…”
mentioning
confidence: 99%
“…In biochar-amended columns, FIB removal was not affected by the presence of an IWS or duration of anteceident dry days (3 versus 7). However, both Afrooz and Boehm (2017) (Hill, Drake et al, 2017). Of the parameters studied, the use of timed-irrigation had the largest negative impact on the greenroof stormwater retention rates.…”
Section: Field Laboratory and Modeling Performancementioning
confidence: 95%